PENGARUH UKURAN PERUSAHAAN, SOLVABILITAS, LABA/(RUGI) OPERASI, DAN OPINI AUDITOR TERHADAP AUDIT DELAY - Regilia Regilia (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2018)
Time difference between financial statement and auditing opinion date indicates the amount of time needed in auditing settlement period. This condition can affect the punctuation of information published and will influence market reaction towards the lengthy information. The study aims to determine the factors that influence audit delay mining sector companies listed at Indonesian Stock Exchange for 2010-2012 period. The factors studied are delay is estimated to affect company size, solvency levels, operation loss and profit, and auditor’s opinion. The population in this study is the mining company’s financial statement listed on the Indonesian Stock Exchange from 2010-2012. Sampling technique with selected sampling by purposive sampling. Of the 40 companies that are mining at Indonesian Stock Exchange from year 2010-2012, there were only 14 companies that meet the characteristics of the samples that have been determined. Data analysis conducted with multiple linear regression model. The results of the study were company size, solvency, operation loss and profit dan auditor’s opinion have significant influence to audit delay simultaneously. Operation loss and profit and auditor’s opinion have significant influence to audit delay partially. But company size and solvency not have significant influence to audit delay partially.